Complexities in colorectal surgery : decision-making and management - Maykel, Justin A.; Champagne, Bradley J.; Orangio, Guy R.; Steele, Scott R. (Springer New York, 2014)
Complexities in Colorectal Surgery: Decision-Making and Management  provides a unique, modern, practical guide that covers the strategic evaluation, specific approaches, and detailed management techniques utilized by expert Colorectal Surgeons caring for patients with complex problems-whether they result from underlying colorectal disease or from complications arising from previous surgical therapy. The text is formatted as both a "how-to" manual as well as an algorithm-based guide allowing the reader to understand the thought process behind the proposed treatment strategies. By making use of evidence-based recommendations, each chapter will include not only diagnostic and therapeutic guidelines, but also a narrative by the author on his/her operative technical details and perioperative "tips and tricks" that they utilize in the management of these complex surgical challenges. This test includes chapters on the assessment of risk and nutritional intervention methods utilized to minimize perioperative complications. In addition, sections on medical and surgical therapies for abdominal, pelvic and anorectal disease are incorporated. Moreover, the technical challenges of managing complications resulting from the original or subsequent operations is addressed. The underlying focus throughout the text is to provide pragmatic and understandable solutions that can be readily implemented by surgeons of varying experience to successfully treat complex colorectal problems. The text also goes beyond the technical aspects of Colorectal Surgery and includes special sections highlighting the essence of a surgeon.  These include chapters describing the importance of the first encounter, building patient rapport, and demonstrating confidence and competence while showing humility and avoiding arrogance.  Additionally, aspects involving the medical-legal, ethical, and economic challenges confronting surgeons are covered.